The Taxonomy and Diversity of Proschkinia (Bacillariophyta), A Common But Enigmatic Genus from Marine Coasts. Issue 4 (23rd April 2020) - Kim, So‐Yeon; Witkowski, Andrzej; Park, Jong‐Gyu; Gastineau, Romain; Ashworth, Matt P.; Kim, Byoung‐Seok; Mann, David G.; Li, Chunlian; Igersheim, Anton; Płociński, Tomasz; Yoo, Yeong‐Du; Chung, Sang‐Ok; et al.
Abstract : Detailed morphological documentation is provided for established Proschkinia taxa, including the generitype, P . bulnheimii, and P . complanata, P . complanatula, P . complanatoides and P . hyalosirella, and six new species. All established taxa are characterized from original material from historical collections. The new species described in this paper ( P . luticola, P . staurospeciosa, P . impar, P . modesta, P . fistulispectabilis, and P . rosowskii ) were isolated from the Western Pacific (Yellow Sea coast of Korea) and the Atlantic (Scottish and Texas coasts). Thorough documentation of the frustule, valve and protoplast architecture revealed the combination of characters diagnostic of the genus Proschkinia : a single‐lobed chloroplast; a broad girdle composed of U‐shaped, perforated bands; the position of the conopeate raphe‐sternum relative to the external and internal valve surface; and the presence of an occluded process through the valve, termed the "fistula". Seven strains of Proschkinia were grown in culture and five of these were sequenced for nuclear ribosomal SSU and plastid‐encoded rbc L. Phylogenetic analysis recovered a clade of Proschkinia with Fistulifera, another fistula‐bearing diatom genus, and together these were sister to a clade formed of the Stauroneidaceae; in turn, all of these were sister to a clade composed of Parlibellus and two monoraphid genera Astartiella and Schizostauron . Despite morphological similarities between Proschkinia and the Naviculaceae, these two taxa are distant in our analysis. We document the variation in the morphology of Proschkinia, including significant variability in the fistula, suggesting that fistula ultrastructure might be one of the key features for species identification within the genus.